The Influence of Job Description, Job Training and Work Experience on Employee Productivity PT XYZ - Yanda Ihza Rizky; Rama Chandra Jaya; Dadan Abdul Aziz Mubarok; Erna Herlinawati; Mochammad Mukti Ali (Dinasti Publisher, 2023)
This study aims to test and analyze the effect of job description, job training and work experience on the work productivity of employees of PT XYZ partially or simultaneously. The data collection method used is interview techniques and distributing questionnaires to respondents. The sample in this study was Non Probability Sampling. The data analysis technique used is multiple linear regression with the SPSS program. Based on the partial test results, job description has a negative and significant effect while job training and work experience have a positive and significant effect on the work productivity of employees of PT XYZ. In simultaneous testing, job description, job training and work experience together have a positive and significant effect on the work productivity of employees of PT XYZ. The coefficient of determination shows that job description, job training and work experience are able to explain the contribution of the influence of job description, job training and work experience on the work productivity of employees of PT XYZ, which is 70.8%, while the remaining 29.2% is influenced by other variables not examined.